2019
DOI: 10.1002/rrq.277
|View full text |Cite
|
Sign up to set email alerts
|

Reading Text When Studying in a Second Language: An Eye‐Tracking Study

Abstract: In this study, we investigated how eye movements are influenced by different text reading goals in participants' first and second language (L1, L2). Participants had to read or study the contents of texts while their eye movements were recorded. One group was asked to read texts in L1 and L2 as they would read any expository text (informative reading). Another group was asked to study L1 and L2 texts for subsequent tests involving true/false questions (study condition). After reading, all participants (includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 65 publications
3
30
0
3
Order By: Relevance
“…Chen and Catrambone (2015) observed that students required on average 18 minutes to study expository texts of 1,000 words in length (56 wpm), although in this study participants had to respond three times to metacognitive prompts. A similar number was found by Dirix, Vander Beken, De Bruyne, Brysbaert, and Duyck (2019): Participants studied at a rate of 54 wpm, whereas they read matched texts at a rate of 189 wpm. Persky and Hogg (2017) reported that their students on average needed 3.2 hours to study 7,500 word textbook chapters on physiology and pharmacokinetics (39 wpm), but studying happened at home (cf.…”
Section: Decrease Of Reading Rate In Old Agesupporting
confidence: 77%
“…Chen and Catrambone (2015) observed that students required on average 18 minutes to study expository texts of 1,000 words in length (56 wpm), although in this study participants had to respond three times to metacognitive prompts. A similar number was found by Dirix, Vander Beken, De Bruyne, Brysbaert, and Duyck (2019): Participants studied at a rate of 54 wpm, whereas they read matched texts at a rate of 189 wpm. Persky and Hogg (2017) reported that their students on average needed 3.2 hours to study 7,500 word textbook chapters on physiology and pharmacokinetics (39 wpm), but studying happened at home (cf.…”
Section: Decrease Of Reading Rate In Old Agesupporting
confidence: 77%
“…Very few studies compare the immediate understanding and learning of new content in a foreign and a native language. Those who do have found either detrimental or null effects of foreign language use, depending on the task [14,15], particularly without foreign language support [16]. These results have been accounted for in the context of cognitive load theory, which suggests a working memory overload for individuals trying to learn content in a language they are not proficient in [16].…”
Section: Introductionmentioning
confidence: 95%
“…A final factor involved is the effort invested in the studying. For bilinguals similar to the ones studied in Experiments 1 and 2, a typical finding is that they require 20% more time to read and study the same materials in L2 than in L1 (Cop et al, 2016; Dirix et al, 2020). So, time pressure is likely to hurt L2 performance more than L1 performance.…”
Section: Discussionmentioning
confidence: 96%